2017
DOI: 10.1111/1756-185x.13122
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin‐37: a new player in Lupus Nephritis?

Abstract: IL-37 level is elevated in SLE patients in comparison to healthy controls and is correlated to high disease activity, mucocutaneous and renal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It was reported the elevated serum levels of interleukin-37 was correlated with poor prognosis in gastric cancer (38). The level of IL-37 in the serum of renal cell carcinoma patients was significantly lower than that in a healthy control group and was negatively correlated with the TNM Classification of Malignant Tumors (TNM) stage of the tumor (39). When IL-37 levels are normal, non-hepatocellular carcinoma tissues are minimal and negatively correlated with the tumor size, microvascular metastasis, and BCLC staging of hepatocellular carcinoma (40).…”
Section: Discussionmentioning
confidence: 98%
“…It was reported the elevated serum levels of interleukin-37 was correlated with poor prognosis in gastric cancer (38). The level of IL-37 in the serum of renal cell carcinoma patients was significantly lower than that in a healthy control group and was negatively correlated with the TNM Classification of Malignant Tumors (TNM) stage of the tumor (39). When IL-37 levels are normal, non-hepatocellular carcinoma tissues are minimal and negatively correlated with the tumor size, microvascular metastasis, and BCLC staging of hepatocellular carcinoma (40).…”
Section: Discussionmentioning
confidence: 98%
“…It exerts critical effects on inflammation and modifies the activation of lymphocytes (L. Wang, Quan, Yue, Heng, & Che, ). Accumulated data have implicated that IL‐37 plays an important role in regulating both innate and adaptive immune responses (Tawfik, Nasef, Omar, & Ghaly, ; Zhao et al, ). In addition, growing bodies of data have revealed that IL‐37 is capable of suppressing the production of inflammatory cytokines, for instance, tumor necrosis factor‐α (TNF‐α) and IL‐6 (L. Wang, Quan, et al, ; L. Wang, Wang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the levels of interleukins in the human body can be used as a diagnostic indicator of the development or progression of many diseases (cancers [ 16 , 17 , 18 , 19 ], heart disease [ 20 , 21 , 22 ] and neurological disorders [ 23 , 24 , 25 ]) affecting contemporary society, including kidney diseases [ 26 , 27 , 28 , 29 , 30 ]. That is why it is extremely important to conduct further extensive scientific and clinical research to assess the biological functions of interleukins and their interactions with other cells of the body, which may lead to health deterioration.…”
Section: Introductionmentioning
confidence: 99%